2021
DOI: 10.1007/s40519-021-01242-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional gastrointestinal symptoms and increased risk for orthorexia nervosa

Abstract: Purpose Recent guidelines point out the possible risk for orthorexia nervosa in functional gastrointestinal disorders, however, to date, no study has investigated this association. The present study aimed to explore the potential relationship between irritable bowel syndrome-related functional gastrointestinal symptoms and certain maladaptive eating behaviours, such as symptoms of orthorexia nervosa and emotional eating. Methods A sample of 644 Hungarian v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
0
12
0
2
Order By: Relevance
“…Clinicians have reported concern regarding disordered eating in DGBI patient cohort. 97 • Recent cross-sectional study of 644 Hungarian volunteers (published since our search was conducted) showed gastrointestinal symptoms were positively associated with orthorexia nervosa and emotional eating 110 • A prospective study of 233 IBS patients commencing a low FODMAP diet found that 23% of patients were classified to be at risk of disordered eating. Adherence to the diet was higher (57%) in those at risk of ED compared to those who were not (35%).…”
Section: Early Data Suggest Link Between Dgbi and Orthorexiamentioning
confidence: 99%
See 2 more Smart Citations
“…Clinicians have reported concern regarding disordered eating in DGBI patient cohort. 97 • Recent cross-sectional study of 644 Hungarian volunteers (published since our search was conducted) showed gastrointestinal symptoms were positively associated with orthorexia nervosa and emotional eating 110 • A prospective study of 233 IBS patients commencing a low FODMAP diet found that 23% of patients were classified to be at risk of disordered eating. Adherence to the diet was higher (57%) in those at risk of ED compared to those who were not (35%).…”
Section: Early Data Suggest Link Between Dgbi and Orthorexiamentioning
confidence: 99%
“… Disordered eating behaviors may precede IBS ED‐related malnutrition impacts electrolyte depletion influencing gastric motility and emptying 103 Refeeding therapy improves gastrointestinal symptoms 104 Bidirectional relationship via brain‐gut axis Anorexia displays different composition and diversity of microbiota compared to controls 105 Anorexia displays higher levels of methane‐producing bacteria linked to slow intestinal transit, 106 similar to differences in microbiota composition seen in patients with IBS compared to healthy controls 107 IBS leads to disordered eating IBS has higher rates of disordered eating behaviors compared to controls, for example, not eating when hungry and vomiting after eating to avoid symptoms, 108 which is correlated with symptom severity 109 Gastrointestinal symptom severity and orthorexia positively correlated 110 …”
Section: Clinical Implications In Gastroenterologymentioning
confidence: 99%
See 1 more Smart Citation
“…Their study found that functional gastrointestinal symptoms were positively associated with symptoms of orthorexia nervosa and emotional eating. The relationship between functional gastrointestinal symptoms and symptoms of orthorexia nervosa was partially mediated by health anxiety [ 19 ]. In this setting, another paper highlighted a bidirectional relationship, since IBS symptoms are more common in patients with established eating disorders [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, preliminary research has found that IBS symptom severity may be positively correlated with orthorexia. 58,64 Various screening tools have been developed to assess risk of ARFID and orthorexia, but none have been validated in IBS. Considering that groundwork research has indicated a relationship between IBS and eating disorders, future research should explore this link further.…”
Section: Psychological Risksmentioning
confidence: 99%